Three Mistakes about Democracy: (translation from English and scientific study by Janusz Grygieńć et al.) - Pettit, Philip; Grygieńć, Janusz (Roczniki Filozoficzne, 2023)
This paper addresses three claims that are often made among contemporary policy-makers, political scientists and political theorists about democracy. The claims, in my view, are false and indeed revealingly false: they display a serious misunderstanding of the nature and appeal of democracy. As we see why they are false, we will come to appreciate dimensions of democracy that easily escape notice. I name the mistakes after outstanding thinkers who have made them. The first I describe as Berlin’s mistake, finding it in the work of the Anglo-Russian philosopher, Isaiah Berlin. The second I describe as Schumpeter’s mistake, naming it after the Austrian-American banker, economist and political thinker, Joseph Schumpeter. And the third I describe as Riker’s mistake, associating it with William Riker, the American political scientist, famous for his distinction between liberalism and populism. The original: Philip Pettit, ”Three Mistakes About Democracy”, in Philosophy and Political Engagement. Reflection in the Public Sphere, ed. Allyn Fives i Keith Breen (London: Palgrave Macmillan, 2016), 187–199. The original article appeared in Kilikya Felsefe Dergisi 2 (2015): 1–13. We thank the Author and the Editors of Kilikya Felsefe Dergisi for their consent to the publication of this translation.